Бистатический лазерный монитор; Письма в Журнал технической физики; Т. 42, № 12 - Тригуб М. В. Максим Викторович; Торгаев С. Н. Станислав Николаевич; Евтушенко Г. С. Геннадий Сергеевич; Троицкий В. О. Владимир Олегович; Шиянов Д. В. Дмитрий Валерьевич (2016, 2016)
Заглавие с экрана